2019
DOI: 10.1111/aji.13089
|View full text |Cite
|
Sign up to set email alerts
|

The underdeveloped innate immunity in embryonic stem cells: The molecular basis and biological perspectives from early embryogenesis

Abstract: Embryonic stem cells (ESCs) have been intensively studied as a promising cell source for regenerative medicine. The rapid advancements in the field have not only proven the feasibility of ESC‐based cell therapy, but also led to a better understanding of pluripotent stem cells (PSCs) as a unique cell population at an early stage of embryogenesis. Recent studies have revealed that both human and mouse ESCs have attenuated innate immune responses to infectious agents and inflammatory cytokines. These findings rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 132 publications
(331 reference statements)
0
16
0
Order By: Relevance
“…IL‐1β is a cytokine produced by joint tissues (unlike LPS); therefore, the rIL‐1β model may be more clinically relevant . In addition, MSCs derived from various tissues may respond differently to inflammation . BMDMSCs are commonly used in equine practice.…”
Section: Discussionmentioning
confidence: 99%
“…IL‐1β is a cytokine produced by joint tissues (unlike LPS); therefore, the rIL‐1β model may be more clinically relevant . In addition, MSCs derived from various tissues may respond differently to inflammation . BMDMSCs are commonly used in equine practice.…”
Section: Discussionmentioning
confidence: 99%
“…While this could be tolerated by tissues of developed organisms, it could cause serious damage to ESCs in an early embryo. From this perspective, an attenuated immunological response could serve as a self-protective mechanism in ESCs by minimizing immunological cytotoxicity at early stages of embryogenesis ( 8 ). From the perspective of ESC biology, IFN response does not appear to be compatible with the pluripotency of ESCs, as demonstrated by a recent study showing that forced activation of the IFN pathway can cause dysregulation of many pluripotency- and lineage-specific genes in ESCs ( 9 ).…”
mentioning
confidence: 99%
“…While ES cells do express other known DNA sensors (e.g. cGAS and STING, data not shown) that in theory can detect intracellular DNAs from infection and DNA damage, their downstream signaling pathways required to activate a robust pro-inflammatory response are absent or highly attenuated, in part due to active suppression by stem cell transcription factors including OCT4 and SOX2 (Eggenberger et al, 2019;Guo, 2019). Nonetheless, studies have indicated that ES cells are hypersensitive to DNA damage and readily undergo differentiation and apoptosis (Aladjem et al, 1998;Heyer et al, 2000).…”
Section: An Alternative Mechanism For Es Cells To Sense Infection Andmentioning
confidence: 99%
“…These cytokines in turn promote the apoptosis and clearance of the affected cells (Jorgensen et al, 2017). Yet, this canonical innate immune pathway is severely attenuated in ES cells and essentially rendered inactive (Guo, 2019). A suppressed innate immune system also suggests that ES cells may lack an effective defense system against pathogen infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation